Transizione ecologica e universo fisico-cibernetico soggetti, strategie, lavoro - Lombardi, Mauro (Firenze University Press, 2021)
There is a growing awareness that humanity and the Planet Earth are near to a tipping point, since we are experiencing a critical transition phase, resulting from a hyper-connected world, where global interactive structures and cumulative feedback evolve. It follows an increasing systemic complexity at all levels, hence uncertainty and instability all decision makers have to deal with. New strategic and operational frameworks are therefore needed. The book aims to provide a theoretical-strategic frame and to suggest he book aims to provide a strategic-operational frame and to suggest both an operational architecture and mechanisms suitable for assessing the effectiveness of strategic choices.
Keywords: Wirtschaftsentwicklung; Critical transition for the Earth-System; Complex innovation Strategies